Implementation of Good Governance as An Acceleration of Public Services at The Village Level - Baskoro Wicaksono; Ali Yusri; Wan Asrida; Wazni Wazni; M. Rafi; Rico Purnawandi Pane (Publikasi Indonesia, 2024)
The slow administrative process, lack of public participation in decision-making, and low transparency and accountability in public financial management are the main problems in public services in Sungai Limau Village, Pusako District, Siak Regency. One of the efforts to improve the service system that still faces various challenges is through the implementation of good governance. This study aims to examine the implementation of good governance in public services in Sungai Limau Village, Pusako District, Siak Regency. This study uses the Focus Group Discussion (FGD) research method. The data collection method in this study involves a review of literature. After the data is collected, the analysis is carried out by filtering relevant data, presenting the data, and finally making conclusions. The findings of the study indicate that the application of good governance principles can accelerate public services at the village level, as seen in Sungai Limau Village, Pusako District, Siak Regency. Therefore, the recommendation that can be taken from this finding is the importance of implementing good governance principles consistently to enhance the standard of public services and boost community engagement and satisfaction.